The tracking of the development and spread of Covid 19 pandemic in the territory of the Taza Province / Morocco - Bouberria, Abdelouahed; Hammimi, Abdelhafid; Abahrour, Mohammed; Errafik, Mohammed (Arab Journal for Sciences and Research Publishing, 2024)
Since the end of 2019, the world has experienced the emergence of the Covid-19 virus, which opened the door to scientific research for contribute to finding alternatives to eliminate and reduce its effects. Global governments have faced this epidemic by developing strategies to protect lives on the one hand and to preserve the structure of the economy and services on the other hand. Universities have engaged by intensifying efforts in scientific research, including the Interdisciplinary College of Taza, through a project that addresses the spatial and social dimensions of Covid-19 in the Taza region, in the context of a partnership with the National Center for Scientific and Technical Research (CNRST). In dealing with this phenomenon, we relied on the geographical approach, based on the daily tracking of the disease in the field and the exploitation of the regional delegate documents in Taza, on the horizon of developing future intervention strategies in the event of such disasters. Moreover, this study led to important results, including the conditions of the spread of the disease in the territory of the region, its area distribution, and its spread in the high population density gatherings.